2015
DOI: 10.1002/ps.4036
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance status of Myzus persicae in Greece: long‐term surveys and new diagnostics for resistance mechanisms

Abstract: The aphid retains costly resistance mechanisms even in the absence of pressure from certain insecticides, which could be attributed to factors related to climate and genetic properties of the populations. The indication of build-up of resistance/tolerance to neonicotinoids, related to CYP6CY3 overexpression, is a matter of concern. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 59 publications
(122 reference statements)
4
57
1
1
Order By: Relevance
“…In our previous study, the R81T mutation was not found in 283 M. persicae s.l. clones collected in Greece during 2012–2013, but P450‐mediated detoxification was found to be involved in the neonicotinoid resistance of the samples examined in that study. The R81T mutation is, however, widespread in populations from peach in southern France, northern Spain and Italy (also in some samples from herbaceous hosts; see Bass et al .…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…In our previous study, the R81T mutation was not found in 283 M. persicae s.l. clones collected in Greece during 2012–2013, but P450‐mediated detoxification was found to be involved in the neonicotinoid resistance of the samples examined in that study. The R81T mutation is, however, widespread in populations from peach in southern France, northern Spain and Italy (also in some samples from herbaceous hosts; see Bass et al .…”
Section: Introductionmentioning
confidence: 71%
“…Resistance genes may be maintained in the parthenogenetic phase of the typical aphid's life cycle during the growing season or in long persistent asexual populations through many years. Indeed, populations/genotypes that exhibit all or most of the resistance mechanisms are not uncommon in Greece and their control with conventional chemical insecticides is becoming difficult . Thus, regular monitoring of the aphid populations accompanied with historical data (see, for example, the evolution of carboxylesterase genes and associated chromosomal rearrangements in the nicotianae populations in Greece) helps to advise for the potential of resistance development and provide information for efficient pest control and resistance management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Foster et al (2007), in their review, cite 13 resistant species, some of them being resistant to six different insecticide groups such as neonicotinoid, pyrethroid and organophosphate insecticides. Among these species important pests are included, such as: M. persicae (Margaritopoulos et al 2007;Kati et al 2014;Voudouris et al 2016Voudouris et al , 2017, A. gossyppii (Shi et al 2011;Herron and Wilson 2011), and Aphis fabae (Scopoli) (Hemiptera: Aphididae) (Ioannidis 2000).…”
Section: Introductionmentioning
confidence: 99%